Evidence for direct effects of glyphosate on ovarian function: glyphosate influences steroidogenesis and proliferation of bovine granulosa but not theca cells in vitro. Issue 6 (5th December 2016) - Perego, Maria Chiara; Schutz, Luis F.; Caloni, Francesca; Cortinovis, Cristina; Albonico, Marco; Spicer, Leon J.
Abstract: Glyphosate (GLY) is a common herbicide used worldwide but its effect on ovarian function in mammals is unknown. The aim of this study was to determine the potential endocrine disruptor effects of GLY on ovarian function evaluating cell proliferation, steroidogenesis and gene expression using bovine granulosa cells (GC) and theca cells as in vitro models. GC proliferation was impaired ( P  < 0.05) after exposure to GLY at 0.5, 1.7 and 5 μg ml −1 . GC progesterone production was not affected ( P  ≥ 0.05) at all doses tested while estradiol production was inhibited ( P  < 0.05) by GLY at 5 μg ml −1 . At the same concentration GLY showed no effect ( P  ≥ 0.05) on theca cell proliferation and steroidogenesis. At higher concentrations (0.01 and 0.3 mg ml −1 ), GLY had no significant effect ( P  ≥ 0.05) on GC proliferation and steroidogenesis. These studies, for the first time, suggest that GLY may affect the reproductive system in cattle via direct action on ovarian function; however, further studies will be required to understand better the mechanism of action and to determine the in vivo reproductive effects of GLY. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Glyphosate (GLY) is a common herbicide used worldwide but its effect on ovarian function in mammals is unknown. The aim of this study was to determine the potential endocrine disruptor effects of GLY on ovarian function evaluating cell proliferation, steroidogenesis and gene expression using bovine granulosa cells and theca cells as in vitro models. Our results, for the first time, suggest that GLY may affect the reproductive system in cattle via direct action on ovarian function.